ChemInform Abstract: Controlled Metal Nanostructures: Fertile Ground for Coordination Chemists. Issue 21 (6th May 2016) - Amiens, C.; Ciuculescu‐Pradines, D.; Philippot, K.
Abstract: Review: 313 refs.